A detailed finite element investigation of the effects of local lateral high-velocity impacts on the ultimate strength of unstiffened steel plates subjected to uniaxial in-plane compression. (January 2021) - Moaieri, Hamid; Khedmati, Mohammad Reza
Abstract: In this paper, the ultimate strength of unstiffened steel plates under uniaxial in-plane compression is numerically studied considering the local lateral impact of a rigid-body impactor. The plates are made of mild steel, where its behaviour is modelled by using the Johnson-Cook material model. The material parameters of the Johnson-Cook material model calibrated by the authors were employed for predicting the behaviour of the target in order to numerically reproduce the impact tests. The value of average in-plane stress of the plates is determined accounting for the collision of rigid-body impactor with masses of 50–150 gr and velocities of 400–1200 m/s. Moreover, the effects of stress waves induced as a result of lateral impact of the rigid-body impactor on the ultimate strength of the plates under uniaxial in-plane compression are also assessed. The results indicate that the ultimate strength of the plate decreases due to stress-wave creation and thus, it is required to take that into account. Besides, it is revealed that assuming the final damaged state of the plate after being laterally impacted by the rigid-body impactor as an initial condition, does not yield a correct response when evaluating its ultimate compressive strength under uniaxial in-plane compression. Highlights: Response of plate models under uniaxial in-plane compression, following the normal impact of a rigid-body impactor is analysed using explicit numerical analysis method. All modelling and analysis issues including initial geometrical imperfections, realistic boundary conditions, material properties, segmentation, detection of damage extent and impact-induced consequences are considered. Average stress-average strain curves and collapse modes at two key strength levels are extracted and interpreted. Three types of relationships are proposed to estimate the ultimate strength of uniaxially in-plane-loaded unstiffened steel plates following the normal impact of a rigid-body impactor.